Music in the Cathedral of Córdoba (1236-16th century) - Benita Cardoso (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
The present article tries to explore the origins of music in the cathedral of Cordoba since it is consecrated as a Christian temple, as well as the beginning and consolidation of the groups and ministers who daily play the Gregorian chant in the Catholic Mass and in the different hours of the divine office, and, extraordinarily, polyphony in the great liturgical solemnities, taking as its starting point the very institution of the cathedral lobby which is the one that makes this sound reality possible. On the other hand, we inquired in the beginnings of the instrumental musical practice from the first news allusive to the presence of the organ and the participation of the first group of minstrels in the solemnity of the religious services, to finish exposing the opinion about the chapel of music that their contemporaries had.